Update on Cactus Pear Breeding and New Products at D*Arrigo Bros. - Bunch, R. (Journal of the Professional Association for Cactus Development, 1997)
D*Arrigo Bros. Co. of California, a grower, packer, and shipper of fresh fruits and vegetables, currently farms about 6000 ha of crops in California and Arizona. We grow, pack, and ship more than 30 different fresh fruits and vegetables, including the well-known vegetables--- lettuce, broccoli, and cauliflower---as well as lesser-known Italian specialty items, such as fennel, broccoli rabe (an Italian mustard green), and, of course, cactus pears.